TIDAL RHYTHMS OF FEEDING IN THE MANGROVE TOPMINNOW, Aplocheilichthys spilauchena (PISCES: CYPRINODONTIDAE) - ANSA, EBINIMI J (Nigerian Journal of Fisheries, 2012)
Sampling was carried out in a mangrove intertidal mud flat, east of Eagle Island, Port Harcourt, Nigeria. A seine net was used in sampling at springtide and neap tide. Two positions at the site - downstream and upstream - were sampled at low and flood tides respectively. A total of 120 specimens of Aplocheilichthys spilauchena ranging from 35 mm to 50 mm total length (TL) were examined. Most specimens collected at low tide had empty stomachs; while most stomachs examined from the flood tide collection had contents. More stomachs contained polychaetes at spring than at neap tide; while mud algae occurred in more stomachs at neap tide than at spring tide. Stomach contents of specimens of A. spilauchena collected from another habitat, the fresh water transition zone of the New Calabar River, revealed the presence of winged ants. These differences in stomach contents of A. spilauchena from different habitats and at different tides indicate that this topminnow species is an opportunistic feeder and feeds on a range of food items depending on availability.